2001
DOI: 10.1001/archneur.58.8.1223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bilateral Subthalamic Stimulation on Cognitive Function in Parkinson Disease

Abstract: Therapy with STN-DBS improves motor symptoms in PD without any clinically relevant neuropsychological deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
145
5
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(172 citation statements)
references
References 33 publications
14
145
5
8
Order By: Relevance
“…Verbal fluency and cognition problems are more often seen in old patients (Hariz et al, 2000;Saint-Cyr et al, 2000;Funkiewiez et al, 2004;Smeding et al, 2011), or in those with poor cognition or depression at baseline (De Gaspari et al, 2006). Specific cognition deficits include impairments of working memory (Saint-Cyr et al, 2000;Higginson et al, 2009;Okun et al, 2009), cognitive processing, visuo-spatial skills and setshifting (Saint-Cyr et al, 2000;Alegret et al, 2001), response inhibition (Witt et al, 2004), or the decoding of facial expressions (Dujardin et al, 2004;Schroeder et al, 2004;Biseul et al, 2005;Drapier et al, 2008). Even when present, the impact of changes in verbal fluency on the quality of life appears to be relatively small (Alegret et al, 2004;Morrison et al, 2004;Montel and Bungener, 2009;Zahodne et al, 2009).…”
Section: Non-motor Side Effects Of Stn and Gpi-dbsmentioning
confidence: 99%
“…Verbal fluency and cognition problems are more often seen in old patients (Hariz et al, 2000;Saint-Cyr et al, 2000;Funkiewiez et al, 2004;Smeding et al, 2011), or in those with poor cognition or depression at baseline (De Gaspari et al, 2006). Specific cognition deficits include impairments of working memory (Saint-Cyr et al, 2000;Higginson et al, 2009;Okun et al, 2009), cognitive processing, visuo-spatial skills and setshifting (Saint-Cyr et al, 2000;Alegret et al, 2001), response inhibition (Witt et al, 2004), or the decoding of facial expressions (Dujardin et al, 2004;Schroeder et al, 2004;Biseul et al, 2005;Drapier et al, 2008). Even when present, the impact of changes in verbal fluency on the quality of life appears to be relatively small (Alegret et al, 2004;Morrison et al, 2004;Montel and Bungener, 2009;Zahodne et al, 2009).…”
Section: Non-motor Side Effects Of Stn and Gpi-dbsmentioning
confidence: 99%
“…Effects of STN‐DBS in cognition and behavior have been analyzed in many studies. The effects of STN‐DBS have been studied with findings ranging from no significant changes in cognition and behavior to mild increase in anxiety and worsening of some cognitive functions (Alegret et al., 2001; Saint‐Cyr, Trépanier, Kumar, Lozano, & Lang, 2000). Some studies found mild improvement in mood such as anxiety and depressive symptoms, but no changes in cognitive performance (Witt et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…16,17,37,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Even among studies reporting more widespread cognitive declines there is disagreement as to the clinical meaningfulness of these changes. Alegret and co-workers 35 interpreted the changes not to be of clinical significance, in contrast to Saint-Cyr et al 38 and Smeding et al 39 As many of the neuropsychological studies of STN DBS have small sample sizes, greater weight should be given to the five controlled neuropsychological studies (excluding studies limited to language or cognitive screening evaluations), even though each has significant methodological and/or conceptual limitations. The first controlled neuropsychological study of STN DBS 45 compared outcomes in eight patients with bilateral STN DBS, eight patients undergoing unilateral pallidotomy and eight unoperated PD patients.…”
Section: Pallidal Deep Brain Stimulationmentioning
confidence: 95%
“…29 Most studies employing formal neuropsychological evaluations have been uncontrolled and used fairly small samples, and methodological limitations of these studies have been reviewed. [30][31][32][33][34] These studies, with few exceptions, 20,[35][36][37][38][39] have observed small and circumscribed cognitive changes, most often in verbal fluency (timed oral word generation according to different phonemic or semantic constraints). 16,17,37,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Even among studies reporting more widespread cognitive declines there is disagreement as to the clinical meaningfulness of these changes.…”
Section: Pallidal Deep Brain Stimulationmentioning
confidence: 99%